Faktor-faktor Yang Mempengaruhi Kualitas Laporan Keuangan Untuk Menunjang UMKM - Lusy Lusy; Yustinus Budi Hermanto; Agung Yohanes (Jurnal Akuntansi dan Pajak, 2022)
This study aims to test the factors that influence the quality of financial statements, on the sustainability of MSMEs. This study explains the effect of human resource competencies, the application of financial accounting standards (SAK) on the quality of financial statements through information technology. This study uses a quantitative approach to test hypotheses. The population of this research is MSME actors on the slopes of Mount Arjuna. Stages of this research method (a) distributing questionnaires; (b) tabulating data; (c) conduct data validation; and (d) conduct data analysis and processing. Data is processed using Smart PLS 2.0. From the results of the R Square value for the quality of financial statements of 0.39. The information technology variable obtained a number of 0.405. The F test results show that the existing model is feasible to be used in this study. Based on the results of hypothesis testing, it was found that (1) the competence of human resources affects the quality of financial statements; (2) the application of SAK affects the quality of financial statements; and (3) Information technology affects the quality of financial statements. The mediation testing shows that information technology does not mediate both human resource competencies and the application of SAK to the quality of financial statements. Keywords : Sustainability, MSME, Quality of Financial Statements..